2014
DOI: 10.1002/2013jb010743
|View full text |Cite
|
Sign up to set email alerts
|

Flow of supersonic jets across flat plates: Implications for ground‐level flow from volcanic blasts

Abstract: We report on laboratory experiments examining the interaction of a jet from an overpressurized reservoir with a canonical ground surface to simulate lateral blasts at volcanoes such as the 1980 blast at Mount St. Helens. These benchmark experiments test the application of supersonic jet models to simulate the flow of volcanic jets over a lateral topography. The internal shock structure of the free jet is modified such that the Mach disk shock is elevated above the surface. In elevation view, the width of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Grad students Mara Orescanin and David Prisco performed studies that showed that for typical vulcanian eruptions and the Mount St. Helens blast, steady flow conditions would have had time to be established . Orescanin et al (2014) demonstrated that internal shock structures within a jet can interact with boundary layers to leave a footprint on the ground that mimics the free jet structure (Orescanin et al 2014). As of this writing the volcanic jet studies continue with Professor Austin's group, now at Caltech, and I am once again back at work on my Old Faithful data and high-speed flow processes.…”
Section: A Time For Consolidation Then Triton and Enceladusmentioning
confidence: 94%
See 2 more Smart Citations
“…Grad students Mara Orescanin and David Prisco performed studies that showed that for typical vulcanian eruptions and the Mount St. Helens blast, steady flow conditions would have had time to be established . Orescanin et al (2014) demonstrated that internal shock structures within a jet can interact with boundary layers to leave a footprint on the ground that mimics the free jet structure (Orescanin et al 2014). As of this writing the volcanic jet studies continue with Professor Austin's group, now at Caltech, and I am once again back at work on my Old Faithful data and high-speed flow processes.…”
Section: A Time For Consolidation Then Triton and Enceladusmentioning
confidence: 94%
“…When scaled up to the dimensions of Mount St. Helens, the model suggested that the supersonic zone extended roughly 11 km to the north (Kieffer 1981a,b). We later revised this distance to 4-9 km by expanding consideration of different possible vent shapes as suggested by Donnadieu & Merle (2001) and pressure ratios (Orescanin et al , 2014. This brought the simple model into reasonable agreement with a detailed supercomputer model that suggests a supersonic zone inside 6 km (Ongaro et al 2011(Ongaro et al , 2012.…”
Section: Mount St Helens 1980 Lateral Blastmentioning
confidence: 99%
See 1 more Smart Citation
“…Another examination of the phenomena exhibited by the Mt St Helens eruption was provided by Orescanin et al (2008). This was an experimental simulation of a supersonic jet impinging on a plane surface.…”
Section: Introductionmentioning
confidence: 99%
“…Notice that the lower part of the Mach disk shock is reduced compared to a free jet. FromOrescanin et al (2014).…”
mentioning
confidence: 99%